AYURVEDA A RAY OF HOPE FOR MULTIPLE SCLEROSIS W.S.R. TO ASTHI MAJJA GATA VATA: A CASE STUDY - Gwala, *Sarla; Kumar Sharma, Mahesh; Prakash Sharma, Gyan (International Journal of Ayurveda and Pharma Research, 2019)
Multiple sclerosis (MS) is a demyelinating disease in which the insulting covers of nerve cells in the brain and spinal cord are damaged. The course of MS is usually relapsing-remitting and sometimes progressive. It is the commonest inflammatory- demyelinating disease of the CNS and the most frequently occurring cause of non traumatic neurologic disability in young and middle aged adults. Immunosuppressant or cortico-steroids as only available treatment in modern science, Ayurveda only the ray of hope. In Ayurveda, multiple Sclerosis can be correlated with Asthi – Majjagatavata. Aim: A case study had been done to find effective management for MS. A 35 year old female patient came to Panchkarma OPD, Dr. S.R. Rajasthan Ayurved University, Jodhpur was suffering from Weakness, Numbness and burning sensation in both arms or legs and Numbness in abdominal region and lack of coordination for 18months.she was diagnosed case of multiple sclerosis (kurtzke disability grade Five) had been given Ayurvedic medicine as well as Panchkarma shown encouraging results. Conclusion: Patient was observed for symptomatic improvement based assessment done by questionnaire, also observed for clinical examination. Patient was also observed for complication during whole course of treatment, untoward complications were not seen. Conservative management of MS through Ayurvedic principles improving the quality of life and decrease dependency of patient. Result: Patient showed improvement kurtzke disability grade Five to grade two.